Design of compounds that increase the absorption of polar molecules - Bowe, Caryn Lang (The National Academy of Sciences of the USA, 1997)
Hydrophilic drugs are often poorly absorbed when administered orally. There has been considerable interest in the possibility of using absorption enhancers to promote absorption of polar molecules across membrane surfaces. The bile acids are one of the most widely investigated classes of absorption enhancers, but there is disagreement about what features of bile acid enhancers are responsible for their efficacy. We have designed a class of glycosylated bile acid derivatives to evaluate how increasing the hydrophilicity of the steroid nucleus affects the ability to transport polar molecules across membranes. Some of the glycosylated molecules are significantly more effective than taurocholate in promoting the intestinal absorption of a range of drugs, showing that hydrophobicity is not a critical parameter in transport efficacy, as previously suggested. Furthermore, the most effective glycosylated compound is also far less damaging to membranes than the best bile acid absorption promoters, presumably because it is more hydrophilic. The results reported here show that it is possible to decouple absorption-promoting activity from membrane damage, a finding that should spark interest in the design of new compounds to facilitate the delivery of polar drugs.